2022
DOI: 10.1007/s40521-022-00320-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Management of Children with Food Allergies

Abstract: Purpose of the Review The purpose of the review is to review the evidence for the nutritional management of paediatric food allergy and provide a practical approach for healthcare professionals working in this area. Recent Findings Dietary elimination remains the mainstay for management of food allergies in children. However, the elimination of food allergens increases the risk for growth faltering, micronutrient deficiencies and feeding difficulties. Brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 121 publications
0
6
0
Order By: Relevance
“…Most CM and egg allergies tolerate processed food associated with a wheat matrix and baked in high temperatures for a prolonged time (180°C for 25 to 30 minutes), which reduces the allergenicity of proteins by denaturing the conformational epitopes present in foods. 9 Once the tolerance to baked goods is confirmed through clinical history and/or oral food challenge, the allergens are allowed to be consumed in this way, respecting the conditions of preparation that guarantee their reduced allergenicity. It is noteworthy that not all processing decreases the allergenicity of food and that even some food sources, when processed, induce greater clinical reactivity.…”
Section: Elimination Diet In the Care Of Food-allergic Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most CM and egg allergies tolerate processed food associated with a wheat matrix and baked in high temperatures for a prolonged time (180°C for 25 to 30 minutes), which reduces the allergenicity of proteins by denaturing the conformational epitopes present in foods. 9 Once the tolerance to baked goods is confirmed through clinical history and/or oral food challenge, the allergens are allowed to be consumed in this way, respecting the conditions of preparation that guarantee their reduced allergenicity. It is noteworthy that not all processing decreases the allergenicity of food and that even some food sources, when processed, induce greater clinical reactivity.…”
Section: Elimination Diet In the Care Of Food-allergic Patientsmentioning
confidence: 99%
“…A crucial topic in FA nutritional therapy is appropriate substitution based on the principles proposed by the Dietary Guides. 9 There are several publications suggesting substitute foods for the main food allergens. However, it is essential to differentiate between types of substitute foods, as they are not all the same.…”
Section: Nutrition For Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…In pediatric patients with a confirmed CMA diagnosis, international guidelines recommend a strict cow's milk protein elimination diet as the only therapeutic strategy to treat CMA. Obviously, the first aim of the elimination diet is to prevent an allergic reaction in CMA patients; but for specialists working in the FA field, avoiding nutritional deficit and ensuring optimal body growth are pivotal aspects that need to be considered [35][36][37][38]. In Table 1 are reported the nutritional intervention cornerstones in CMA pediatric patients.…”
Section: Nutritional Strategies For the Management Of Cow's Milk Allergymentioning
confidence: 99%
“…Whey protein (WP) not only boosts immunity due to the presence of β-lactoglobulin (β-LG), α-lactalbumin (αLA), bovine serum albumin, lactoferrin (LF), immunoglobulin (Ig), enzymes, and glycomacropeptide, and is also a source of essential amino acids (Marshall, 2004). Though it is obvious that WP is an excellent nutritive food, some of its components have been linked to allergic conditions in infants and young children (Jaiswal and Worku, 2022;Wright et al, 2022). Among the above mentioned proteins, the major antigens include casein, β-LG, and αLA, and it has been reported that most patients allergic to milk allergy have specific IgE antibodies against at least two antigens (Cohen et al, 2022;Savilahti and Kuitunen, 1992;Sicherer and Sampson, 1999).…”
Section: Introductionmentioning
confidence: 99%